Assessing Engineering Behavior of Fly Ash-Based Geopolymer Concrete: Empirical Modeling - Ahmad B. Malkawi (Infrastructures, 2025)
The present work investigates the characteristics of fly ash-based geopolymer concrete (GPC) in terms of compressive, splitting, and flexural strength, elasticity modulus, and stress–strain relationship. Datasets including 726 observations were collected from the sorted literature, and regression models were proposed. These models were then validated using experimental results obtained from 12 different mixtures prepared and tested in this research. Finally, the models were compared with the current models of several codes for ordinary Portland cement (OPC) concrete. The proposed models provided good accuracy with a determination coefficient greater than 60% for all models; such a value is considered large enough for big datasets. The behavior of GPC is not well-represented by OPC concrete standards, and GPC also displays a lower elastic modulus at similar strength. A constitutive model is proposed to describe GPC’s full stress–strain response, with the resulting equations providing relatively accurate predictions of its mechanical behavior. Compared to OPC concrete, GPC shows notably greater deformation, characterized by a wider range and higher average for both strain at peak stress (mean 0.00296) and ultimate strain (mean 0.01002). This work’s results may prompt further detailed research on GPC’s mechanical and, importantly, structural behavior.